Analisis Stilistika dalam Novel Orang-Orang Biasa Karya Andrea Hirata - Nazari, Fadiah; Shomary, Sudirman (UIR Press, 2024)
Language as a literary medium demands uniqueness and finesse in its usage, reflected in literary language that has been tailored by authors to achieve beauty. Stylistics becomes crucial in examining the beauty and precision of language use, even in non-literary contexts. This study aims to analyze the syntactic, lexical, and figurative language structures in the novel